Distributed clean energy opportunities for US oil refinery operations - Krah, Kathleen; Ericson, Sean; Li, Xiangkun; Olawale, Opeoluwa Wonuola; Castillo, Ricardo; Newes, Emily; Engel-Cox, Jill (Frontiers in Energy Research, 2023)
The oil and gas industry is increasingly seeking operational improvements to reduce costs and emissions while improving resilience. This study describes techno-economic analysis of opportunities for distributed energy resources that could be integrated to support oil and gas companies' economic, environmental, and energy resiliency goals. Specifically, the analysis evaluates solar photovoltaics, wind turbines, battery energy storage, landfill gas, biomass, municipal solid waste-to-energy, solar steam for process heat, combined heat and power, and electrolyzers for hydrogen production at two hypothetical refineries, one located in Louisiana and the other in southern California. These technologies could reduce the sites' consumption of grid electricity and/or natural gas and thus can help reduce emissions. For each emissions reduction scenario, a cost of avoided emissions was calculated; these values can be compared to internal organizational value placed on emissions reductions, to other emissions reduction strategies such as energy efficiency, reducing flaring, and direct carbon capture and sequestration, and to existing (albeit limited) U.S. carbon markets such as California's Low Carbon Fuel Standard. Results indicate that the associated costs of emissions reductions via several distributed clean energy technologies are competitive with these options and markets under certain conditions. The study also explores the ability of onsite distributed energy resources to improve site resilience to electric utility outages. This is a provisional file, not the final typeset article also contribute significantly to global emissions, estimated at 15% of energy-related (IEA, 2020) and 9% of global (Gargett et al., 2019) GHG emissions. Thus, many companies in the oil and gas sector are setting goals to reduce their carbon footprints and investigating pathways to achieve these goals at least cost.